Village-Owned Enterprise Strategy in Improving the Economic Welfare of Sustainable Farmers - Habib, Fadlan; Kiswanto, Eddy (Center for Populatioan and Policy Studies Universitas Gadjah Mada, 2024)
This research analyzis the role of BUMDes and other multi-stakeholders in efforts to improve the welfare of farmers in rural areas. The research uses qualitative methods with explanation analysis techniques. The results of the research show that the problems faced by farmers are largely influenced by middlemen’s play in determining prices which has an impact on farmers’ losses, apart from that, it is also influenced by the lack of access to information related to the market. For this reason, the village government is trying to create an agricultural business unit under the auspices of BUMDes which provides assistance to farmers in the form of capital support, marketing and also providing market guarantees. This innovation is considered successful in improving farmers’ livelihoods and welfare. The agricultural economic development process carried out by BUMDes is basically the result of collaborative work carried out jointly with farmers, the private sector and supra-villages. An institutional pattern built on trust, transparency and strong commitment is the key to their success in building collaborative governance.